Digitalization of Agriculture-The Future of Indian Agriculture - Kumar, Amitosh; Kumar, Anshuman; M. R. Vineeth (Journal of Agricultural Extension Management, 2021)
Digitization and e-agriculture opens up opportunities for traditional nonplayers in the agriculture value chain. It provides reliable data for research and policy-making and fills the current information gap. Farmers’ income can be increased, and positive effects on agriculture are seen through the emergence of farm technologies and connected robust information communication technology (ICT). Digital transformation will provide access to finance through exposure and awareness due to digitization, forecasts on climate change enable right decisions, for better soil fertility and soil structure, access to markets, access to information, smallholdings utilization and enables predictive analysis. Adopting a holistic ecosystem approach to address challenges faced by the Indian agriculture sector is of national interest to achieve objectives, like doubling farmer incomes and sustainable development. Finally, digitization will change the scène of Indian agriculture in the future and guarantee higher income to farmers and reduce distress. This paper explains the scope of digitization in agriculture and reviews the on-going digital agricultural and e-agriculture initiatives